Epstein–Barr Virus Expression in Classic Hodgkin Lymphoma in an Indian Cohort and its Association with Clinical and Histomorphological Parameters - Rani, Preeti (Indian J Hematol Blood Transfus, 2020)
Epstein Barr virus (EBV) associated Hodgkin lymphoma (HL) has been defined as cases with clonal EBV infection, EBV genome and gene products in the Reed Sternberg cells. We evaluated the prevalence and clinico-pathological association of EBV in North Indian HL patients. Eighty-eight cases of histologically confirmed classic HL were evaluated for EBV by both IHC expression of LMP1 and real time PCR on formalin fixed lymph node tissue. The expression pattern was analyzed for any association with clinical and histomorphological parameters. Nodular sclerosis subtype was seen in 79.5% patients and mixed cellularity was seen in the remaining patients. Ninety percent of the cases were positive for EBV. The detection rate of EBV by IHC was higher. The EBV positive cases presented with higher disease stage (p < 0.05). The presence of histomorphological features like granuloma formation (5/5), atypical lymphocytes (8/8), histiocyte clusters (26/28), large area of necrosis (11/12), less prominent inflammatory response (25/27) was associated with EBV positivity (p > 0.05). In our study population a high proportion of HL cases showed positivity for EBV indicating a pathogenic role. The positivity was independent of age, gender and histological subtype. Further evaluation of EBV positivity in modulation of tumor immunity may provide insights into variable treatment outcome in EBV positive cases.